2018
DOI: 10.1177/1934578x1801300313
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling and Chemical-Based Antioxidant Assays of Green and Red Lettuce (Lactuca sativa)

Abstract: Lettuce (Lactuca sativa) is an important leaf vegetable crop worldwide. The total phenolic content was higher in the red skirt methanol extracts with a level of 64.9 ± 0.3 mg GA/g, and phenolic content of green skirt was 49.4 ± 0.3 mg GA/g. The total flavonoid content in the methanol extract of red skirt showed the highest concentration (291.6 ± 9.0 mg rutin/g), followed by green skirt (223 ± 9.8 mg rutin/g). The red skirt showed a higher content of anthocyanin (23.7 ± 0.8 mg/100 g) compared to the green skirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…The elevated antioxidant activity of F5 and F9 may be due to the increase of banana and onion peels as well as lettuce and whey protein in the formulation especially that these ingredients have potent antioxidant activities as confirmed by Park et al (2018) and Mohamed et al (2019). Values are mean of three replicates ± SD, number in the same column followed by the same letter is not significantly different at 0.05 level; ND: Not detected Color is one of the most important quality features of vegetable and fruit products, where it is the first thing consumers see (Sudha et al, 2015).…”
Section: Physiochemical Characteristics Of Different Soup Mixturesmentioning
confidence: 82%
“…The elevated antioxidant activity of F5 and F9 may be due to the increase of banana and onion peels as well as lettuce and whey protein in the formulation especially that these ingredients have potent antioxidant activities as confirmed by Park et al (2018) and Mohamed et al (2019). Values are mean of three replicates ± SD, number in the same column followed by the same letter is not significantly different at 0.05 level; ND: Not detected Color is one of the most important quality features of vegetable and fruit products, where it is the first thing consumers see (Sudha et al, 2015).…”
Section: Physiochemical Characteristics Of Different Soup Mixturesmentioning
confidence: 82%
“…The findings are consistent with a previous study reporting that in radish ( Raphanus sativus ), the red variety showed higher antioxidant activity than white radish [ 58 ]. Moreover, in lettuce ( Lactuca sativa ), red varieties also contain higher amounts of total phenolics, flavonoids, anthocyanins, and carotenoids, and thus also showed higher antioxidant activities than green lettuce [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pH differential method, consisting of KCl buffer (0.025 M, pH 1.0) and CH 3 COONa buffer (0.4 M, pH 4.5), was used to measure the total anthocyanin content in the prepared crude extract of each sample [ 59 ]. Aliquots of 1 mL of the extract were mixed with 4 mL of each of the buffers, and incubated at 28 °C for 15 min for equilibration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total anthocyanin contents were evaluated using the pH differential method [39]. A 1 mL aliquot of the extract was mixed with 4 mL of each of two buffers (CH 3 COONa buffer [0.4 M, pH 4.5] and KCl buffer [0.025 M, pH 1.0]), followed by incubation at 28 • C for 15 min.…”
Section: Determination Of Total Anthocyanin Contentsmentioning
confidence: 99%